Infinitely Many High Energy Solutions for Kirchhoff-Schrödinger-Poisson Equation with 4-Superlinear Growth Condition - Sha Li; Ziheng Zhang (Journal of Advances in Applied & Computational Mathematics, 2019)
In this article we study the following nonlinear problem of Kirchhoff-Schrödinger-Poisson equation with pure power nonlinearity where a,b and V are positive constants, and 3<p<5. Using the fountain theorem, we obtain infinitely many high energy radial solutions, where some new tricks associated with the scaling technique are introduced to overcome the difficulty caused by the combination of two nonlocal terms.